The derivative of sec-112x2 - 1 with respect

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

981.

Find C of Lagrange's mean value theorem for the function f(x) = 3x2 + 5x + 7 in the interval [1, 3].

  • 73

  • 2

  • 32

  • 43


982.

For f(x) = (x - 1)2/3, the mean value theorem is applicable to f(x) in the interval

  • [2, 4]

  • [0, 2]

  • [- 2, 2]

  • any finite interval


983.

The differential coefficient of f(log(x)) with respect to x, where f(x) = log(x) is

  • xlogx

  • logxx

  • xlogx- 1

  • None of these


984.

If f(x) = x + - x, x  2λ,                 x = 2, then f is continuous at x = 2, provided λ is equal to

  • 1

  • 0

  • - 1

  • 2


Advertisement
Advertisement

985.

The derivative of sec-112x2 - 1 with respect to 1 - x2 at x = 1/2 will be

  • 1/4

  • sec-114

  • 4

  • 0


C.

4

Let y = sec-112x2 - 1and z = 1 - x2Put x = cosθ  y = sec-112cos2θ - 1         = sec-11cos2θ         = sec-1sec2θ = 2θand z = 1 - cos2θ = sinθOn differentiating w.r.t. θ, we get dy = 2 and dz = cosθ  dydz = dydz = 2cosθ = 2x dydzx = 12 = 212 = 4


Advertisement
986.

If x = acos3θ, y = asin3θ, then 1 + dydx2 is equal to

  • tan2θ

  • secθ

  • sec2θ

  • secθ


987.

ddxcot-1x is equal to

  • 11 + x2

  • - 11 + x2

  • 11 + x2

  • - 11 + x2


988.

The value of 12. upto three places of decimals using the method of Newton-Raphson, will be

  • 3.463

  • 3.462

  • 3.467

  • None of these


Advertisement
989.

If fx = log1 + x1 - x and gx = 3x +x31 + 3x2, then fog(x) is equal to

  • - f(x)

  • 3f(x)

  • [f(x)]3

  • None of these


990.

Let f(x) be differentiable on the interval (0, ) such that f(1) =1 and limtt2fx - x2ftt - x = 1 for each x > 0. Then, f(x) is equal to

  • 13x + 23x2

  • - x3 + 4x23

  • - 1x

  • - 1x + 2x2


Advertisement